Aves de Quindicocha - Valle de Sibundoy, Putumayo - Colombia: Potencial área de conservación - Acevedo-Charry, Orlando A.; 1 Corporación para el desarrollo sostenible del sur de la amazonia – CORPOAMAZONIA. Unidad Territorial Andino-Amazónica, Sibundoy, Putumayo, Colombia. 2 Tropical Community Ecology Lab, University of Puerto Rico – Río Piedras, College of Natural Science. Department of Biology. Lab. CNC-309. San Juan, Puerto Rico*. 3 Grupo de Ornitología de la Universidad Nacional - GOUN. Colección de Ornitología, Instituto de Ciencias Naturales, Facultad de Ciencias, Universidad Nacional de Colombia. Edificio 425, laboratorio 218. Bogotá, D. C., Colombia. (2013)
Knowledge of the existing biodiversity is the basis of conservation. To establish Area of Important Bird Area (IBA) in the valley of Sibundoy (department of Putumayo, Quindicocha territory, in the southwest of Colombia). I conducted 21 days of birding in 11 areas between May and June 2013. I recorded 164 bird species; nine of these species correspond to distribution amplitudes or confirmations in the region. The results support the request to designate this region as an IBA, independent to IBA Laguna de la Cocha. It meets the BirdLife International criteria regarding the presence of endangered species - A1 (Hapalopsittaca amazonina; Grallaria rufocinerea; Doliornis remseni; Sericossypha albocristata; Buthraupis wetmorei; Hypopyrrhus pyrohypogaster), the presence of seven birds restricted to five Endemic Bird Areas (EBAs) - A2, and the presence of 27 species of birds restricted to the North Andes biome - A3. Some of the species not included for IBA Laguna de la Cocha.